Parents' opinions and sources of information on immunization in children - Agata Anna Salwa (Kazimierz Wielki University, 2017)
Summary Introduction and purpose of the work. By introducing new vaccines into the vaccination program, an important part of the education of the public in the prevention of infectious diseases is an important element. In order to properly distribute information about vaccination, it is necessary to know how parents and parents receive information. The purpose of the study was to learn parents' opinions and sources of information on childhood vaccination. Material and methods. The study was conducted in 2017 from January to mid-June. 104 people, fathers and mothers were examined. The diagnostic survey method was used in this study. In the next stage of the research, the survey technique was used. The research tool used in the study was a questionnaire, which contained 40 questions and consisted of two parts. Results. Studies have shown a significant correlation between education and sources of information on child immunization. A positive opinion about vaccination was expressed by 41.3%. A significantly lower percentage of respondents rated their vaccination as negative 3.8%. In the majority of respondents with primary / vocational education, the highest percentage of respondents rated their knowledge as low 37.5% or an average of 29.2%. Conclusions. Despite their doubts about their effectiveness and safety, parents expressed their positive opinion about the use of immunization in children. Increase physician activation as they are the primary source of health information for parents.